Validation of a methodology to implement Lean Production in Textile and Clothing Industry - Maia, Laura Costa (2018)
Lean Production is considered a management methodology that has been implemented in many industries and services. Nevertheless, Lean experts know that this is not only a management methodology; it is more a philosophy and a new way of life. This is the reason why it is difficult to implement but, even worst, to be successful and to be sustainable. A continuous effort of improvement must always be kept in mind. Attending to these factors, it is important to have a methodology that helps to implement Lean Production effectively. This methodology could be different from industry to industry in order to model the differences between them and, most important, to assure its sustainability. This paper presents the validation of one such methodology for the Textile and Clothing Industry (TCI), based on three case studies (three Textile and Clothing companies located in North of Portugal). To validate it, different field procedures instruments such as interviews, questionnaires, and checklists were used. With these instruments, some validation results of the methodology were obtained, mainly, related with the diagnosis phase of Lean implementation. Results of two case studies were published in previous papers, being the results of a third case presented in this paper. Also, an analysis and discussion of the three case studies results, regarding their attitudes and difficulties are presented.